Chronic rejection after lung transplantation Overview and experimental approaches for long-term organ protection - Gräbner, Cindy; Ramsperger-Gleixner, Martina; Kuckhahn, Annika; Weyand, Michael; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2023)
Background Following lung transplantation (LTx) 50% of all patients develop chronic rejection within 5 years of transplantation in the form of a chronic lung allograft dysfunction (CLAD). To date, the processes of chronic transplant failure are not curable with medication.Material and method After illustrating the different phenotypes and pathogenesis of CLAD, this review focuses on the diagnostic and treatment options. New clinical and experimental treatment approaches for CLAD are discussed.Results For research of new experimental treatment options, animal models are being used. The established model for CLAD research is the orthotopic tracheal transplantation in mice. Using this model, the influence of the chemokine receptor M33 of the murine cytomegalovirus on the development of chronic rejection and its persistence in the body could be shown. Furthermore, the antiplatelet agent clopidogrel, the mTOR inhibitor everolimus and the tyrosine kinase inhibitor nintedanib reduced the development of the rejection-induced histological changes in tracheal allografts in mouse models.Conclusion The successful experimental approaches show potential treatment approaches, which counteract the development of a CLAD and have to go through clinical trials before they can be used on patients after lung transplantation.
CRIS-Team WoS Importer:2023-03-10